Congenital cerebriform intradermal nevus presenting as cutis verticis gyrata: a case report - Jawarkar, Ashish; Gharia, Bhumika J.; Shah, Amrish N. (International Journal of Research in Medical Sciences, 2018)
Cerebriform intradermal nevus is a rare disorder characterised by development of folds and furrows on the scalp, giving it a convoluted appearance resembling surface of the brain. There are two main forms of CVG, primary and secondary. Secondary form may appear at any age and is usually secondary to causes such as tumors, Cerebriform intradermal nevus (CIN), neurofibromas or amyloidosis. There is high risk of development of malignant melanoma in patients of CIN presenting as CVG. Hence early diagnosis and treatment is important.